ANALISA KAPASITAS DAN TINGKAT KINERJA SIMPANG BERSINYAL (STUDI KASUS SIMPANG TIGA PURWOSARI KABUPATEN PASURUAN) - Esti Widodo (Universitas Tribhuwana Tunggadewi Malang, 2016)
Signaled Purwosari T-junction Pasuruan is one of the intersections in Pasuruan with moderately crowded traffic as the main road connecting Surabaya - Malang and Pasuruan - Malang. Its current status requires an evaluation and a performance optimization. The primary data used for the analysis was obtained through field surveys, while the performance analysis using MKJI 1997 methods. Based on the final results of the analysis can be concluded, the level of performance intersection experiencing saturation and congestion, especially the direction from Surabaya to Malang. To obtain optimal performance of the intersection, do some alternative solutions changing light signal cycle and adding approached width. Alternative lights signal cycle change are the best solution in terms of cost because it is easy and fast, compared to adding approached width.